What's the problem with patient experience feedback? A macro and micro understanding, based on findings from a three‐site UK qualitative study. (22nd September 2018) - Sheard, Laura; Peacock, Rosemary; Marsh, Claire; Lawton, Rebecca
Abstract: Context: Collecting feedback from patients about their experiences of health care is an important activity. However, improvement based on this feedback rarely materializes. In this study, we focus on answering the question—"what is impeding the use of patient experience feedback?" Methods: We conducted a qualitative study in 2016 across three NHS hospital Trusts in the North of England. Focus groups were undertaken with ward‐based staff, and hospital managers were interviewed in‐depth (50 participants). We conducted a conceptual‐level analysis. Findings: On a macro level, we found that the intense focus on the collection of patient experience feedback has developed into its own self‐perpetuating industry with a significant allocation of resource, effort and time being expended on this task. This is often at the expense of pan‐organizational learning or improvements being made. On a micro level, ward staff struggled to interact with feedback due to its complexity with questions raised about the value, validity and timeliness of data sources. Conclusions: Macro and micro prohibiting factors come together in a perfect storm which provides a substantial impediment to improvements being made. Recommendations for policy change are put forward alongside recognition that high‐level organizational culture/systems are currently too sluggish to allow fruitful learning and action to occur from the feedback that patients give.